Family planning impact evaluation: the evolution of techniques - Albert I. Hermalin (Población y Salud en Mesoamérica)
This paper is a slightly revised version of a paper prepared for the seminar on methods for impact evaluation of family planning programs held in Jaco, Costa Rica, May 14-16, 1997. The seminar was sponsored by the International Union for the Scientific Study of Population (IUSSP), the United States Agency for International Development (USAID), the Carolina Population Center of the University of North Carolina, and the Central American Population Program of the University of Costa Rica. The goal of the seminar was to look at current methodological problems facing careful evaluation of the impact of programs, to examine some of the new methods that have been developed to address persistent issues, and to assess the methodological challenges posed by the expanded goals of many programs following the 1994 Cairo International Conference on Population and Development. This paper was designed to serve as the background to discussions of current methodologies and issues by tracing the development and nature of methods for assessing impact that started soon after the first programs were initiated in the 1950s. The techniques discussed include standardization and trend analysis, the analyses of acceptor data, experimental designs, multivariate areal analysis, population-based surveys, and multilevel strategies. The intent of the program sponsors and coordinators was to publish the collected papers but various contingencies intervened to make this infeasible. A description of the seminar and many of the papers are maintained on the University of Costa Rica website: http://ccp.ucr.ac.cr/noticias/plani/iusspi.htm. As a background chapter, the original version contained references to many of the other chapters planned for the volume. As many of these papers appear on the website, relevant references are given to the authors and this website throughout the paper.